2021
DOI: 10.55563/clinexprheumatol/p1q482
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of microvascular involvement in lupus nephritis patients by retinal OCT-angiography and kidney biopsies

Abstract: ObjectiveOcular and renal microvascular damage in lupus nephritis (LN) share similar physiopathological pathways that have investigated using traditional fundus examination and high-resolution colour electroretinography. Optical coherence tomography angiography (OCTA) is a recent, non-invasive technique for imaging the microvasculature of retina and choroid. Aim of the study was to investigate through OCTA analysis the relationship between retinal microvasculature alterations and renal function and histologic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
6
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 21 publications
1
6
1
Order By: Relevance
“…Meanwhile, due to the similarity in anatomy and physiology between the brain and eye, when the central nervous system is involved, retinal tissue may also be about to enter the pathological stage, with FAZ morphology becoming more irregular and VD showing a downward trend. The negative results of the renal system in this study were opposite to Conigliaro et al.’s study ( 36 ). Therefore, future studies with larger sample sizes are needed to validate the associations that were found in this study.…”
Section: Discussioncontrasting
confidence: 99%
“…Meanwhile, due to the similarity in anatomy and physiology between the brain and eye, when the central nervous system is involved, retinal tissue may also be about to enter the pathological stage, with FAZ morphology becoming more irregular and VD showing a downward trend. The negative results of the renal system in this study were opposite to Conigliaro et al.’s study ( 36 ). Therefore, future studies with larger sample sizes are needed to validate the associations that were found in this study.…”
Section: Discussioncontrasting
confidence: 99%
“…More and more researchers are using OCTA to study the fundus microvascular changes in SLE patients. [8][9][10][11][12][13][14][22][23][24][25][26][27][28][29][30] However, many researchers have found inconsistent results (Table 5). 8,11,13,26,27 In this study, we first evaluated the alterations of pVD in a circular area of F2.5 mm, F3.5 mm, and F5.0 mm, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…It has been investigated in the past for its ability to detect preclinical vascular damage in systemic diseases such as diabetes, arterial hypertension and chronic kidney disease. 8 A relationship between retinal microvascular alterations and CV risk profile was also underlined in patients with coronary artery disease, but further studies is this field are needed. 9 Recently, subclinical retinal microvascular impairment evaluated through OCTA has been detected in patients with SLE compared with HCs.…”
Section: Lupus Science and Medicinementioning
confidence: 99%
“…10 Moreover, a correlation between retinal microvascular alterations, kidney function parameters and vascular lesions detected at kidney biopsy was assessed in a lupus nephritis cohort. 8 A relationship between IMT and reduced OCTA retinal vascular density has been identified in systemic diseases, such as hypertension and diabetes. 11 12 Therefore, we hypothesised that retinal microvascularisation could reflect systemic vascular damage in SLE.…”
Section: Lupus Science and Medicinementioning
confidence: 99%